Determinan Kepuasan Kerja : Implikasi Terhadap Kinerja Pegawai Pada Kelurahan Se Kecamatan Teluk Bayur - Istifari, Putri Ayu; Maswanto, Maswanto; Nuraeni, Nuraeni (Dinasti Research, 2024)
This research aims to determine the determinants of job satisfaction and the implications for employee performance in sub-districk in Teluk Bayur Districk East Kalimantan. The research method used in this research is a quantitative method with an associative approach. The number of research respondens used was 68 ASN ( Civil Service ) employes in sub-districts in Teluk Bayur District, East Kalimantan.The ssampling with a saturated sample approach because the entire population was taken as a sample. The result of the research are (a)leadership has a significant effect on job satisfaction, (b) organizational culture has an insignificant effect on job satisfaction, (c) leadership has a significant effect on employee performance, (d) organizational culture has an insignificant effect on employee performance, (e) job satisfaction has a significant effect on employee performance, (f) job satisfaction has succeeded in mediating the influence of leadership on employee performance, and (g) job satisfaction has not succeeded in mediating the influence of organizational culture on employee performance.